PENGARUH PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN TAMU MEMILIH HOTEL IBIS MANADO CITY CENTER BOULEVARD - Hanafi Wowiling; Agustinus Walansendouw; Claurensya Maramis (Jurnal Hospitaliti, 2022)
This study aims to determine: the effect of social media promotions on the decision of guests to choose the Ibis Manado City Center Boulevard hotel. This study uses a quantitative method with a simple regression model. The population in this study are guests who stay or use the services of the Ibis Manado City Center Boulevard Hotel. The sample size taken was as many as respondents which were determined based on Roscoe's opinion. By using a type of nin probability sampling where the sampling is not fully carried out using the law of probability. This means that not all population units have the opportunity to be used as research samples. All data was collected using surveys and questionnaires. Questionnaires are made based on the dimensions of each variable. Thus, the results Y = 3.-32 + 0.896X were found, which indicated that any increase in the X variable would cause an increase in the Y variable. Similarly, using correlation coefficient analysis, it was found that r = 0.948 showed that the correlation coefficient of determination was found to be r2 = 0.899, which means that the guest's decision to choose due to the strong influence of social media promotion of 89.9% and the remaining 10.1% is the influence of variables not examined of 65.61%. The remaining of 34.39% were other factors that were not observed, namely the lack of food and beverage equipment, the lack of diversity in the menu served, and the lack of communication and care from the leadership.